Ziekenhuis in discussie. [Met inl. van M.T. Feitsma-Eisma. Met bijdrn van A. Querido, A.J.M. Karthaus, L.C. Wesseldijk e.a.] (Documentie- en Informatiecentrale, 1971)
Met afbn, bibliogr., grafn, prt en tabn.